2009
DOI: 10.1063/1.3266508
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cooperativity in the dynamics of glass-forming systems: A new insight

Abstract: The mechanism behind the steep slowing down of molecular motions upon approaching the glass transition remains a great puzzle. Most of the theories relate this mechanism to the cooperativity in molecular motion. In this work, we estimate the length scale of molecular cooperativity xi for many glass-forming systems from the collective vibrations (the so-called boson peak). The obtained values agree well with the dynamic heterogeneity length scale estimated using four-dimensional NMR. We demonstrate that xi dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(123 citation statements)
references
References 59 publications
15
106
1
1
Order By: Relevance
“…Given Eq. (39), and that prior experiments [13] generically found V # (T )  ln  (T ) in the deeply supercooled regime consistent with our theory, an effective barrier proportional the "number of correlated molecules" can be viewed as a logical inference of the ECNLE approach. However, the notion of a number of correlated particles determining the barrier, a central concept of models based on compact domains of re-arranging particles, does not directly enter ECNLE theory.…”
Section: Pressure Effects and Growing Cooperative Length Scalesupporting
confidence: 88%
See 2 more Smart Citations
“…Given Eq. (39), and that prior experiments [13] generically found V # (T )  ln  (T ) in the deeply supercooled regime consistent with our theory, an effective barrier proportional the "number of correlated molecules" can be viewed as a logical inference of the ECNLE approach. However, the notion of a number of correlated particles determining the barrier, a central concept of models based on compact domains of re-arranging particles, does not directly enter ECNLE theory.…”
Section: Pressure Effects and Growing Cooperative Length Scalesupporting
confidence: 88%
“…Very interestingly, the activation volume appears to be tightly correlated with measures of dynamic heterogeneity and correlation. Specifically, the cube root of the activation volume at T g has been shown to correlate with the characteristic length scale of the Boson peak [13,14]. In addition, V # (T ) appears to have the same temperature dependence as the number of correlated molecules, N corr (T ) , as extracted from nonlinear dielectric measurements for glycerol [62].…”
Section: Pressure Effects and Growing Cooperative Length Scalementioning
confidence: 82%
See 1 more Smart Citation
“…also accords with the typical "cooperative motion scale" from neutron and Raman scattering, Boson peak, and NMR measurements. 75 In addition, the inset of Fig. 8 shows that the predicted low T limit of G/ μ = L/L A from our model is compatible with the experimentally observed behavior of several glass-forming liquids.…”
Section: B Living Polymerization Model Of Stringssupporting
confidence: 84%
“…As a result, simulations are likely to miss some of the complex features associated with highly cooperative 44 and spatially heterogeneous dynamics 43,[45][46][47] . For example, while constant stress experiments have shown that polymer segmental dynamics during plastic flow become substantially more spatially homogeneous 20 , this feature is much less prominent in computer simulations 48 .…”
Section: Comparison To Theory Chen and Schweizer Have Developed A Momentioning
confidence: 99%